(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article presents a lexical and semantic analysis of lexical units in the diplomatic texts in the Uzbek language, revealing a number of their lexical and semantic characteristics. A detailed analysis of the similarities and differences in terms used in diplomatic texts or in the naming of written documents and correspondence is reflected in the article.